Exploring differences in perceptions of gentrification, neighborhood satisfaction, social cohesion, and health among residents of two predominantly African American Pittsburgh neighborhoods (n = 60) - Alexandra Mendoza-Graf; Sarah MacCarthy; Rebecca Collins; La'Vette Wagner; Tamara Dubowitz (BMC, 2023)
Abstract Background Gentrification often leads to changes in the social and physical environment of neighborhoods, which social capital theory has found are connected to aspects of resident health and wellbeing. A growing body of literature has explored the impact of gentrification on health and wellbeing of residents. The goal of this study is to qualitatively explore the ways in which gentrification may have impacted perceptions of neighborhood satisfaction, social cohesion, and health of neighborhood residents (n = 60) from two predominantly Black neighborhoods in Pittsburgh, Pennsylvania, one of which experienced Black gentrification during the study's time period. This analysis is unique in its ability to capture experiences of residents who remained in their neighborhood throughout the course of the study, as well as those who moved away from their neighborhood. Methods Participants were randomly selected from a larger cohort enrolled in a quasi-experimental study and categorized by whether they lived in a census tract that gentrified, whether they owned or rented their home, and whether they moved from the neighborhood or remained in the same place of residence between 2011 and 2018. Phone interviews lasting approximately 30 min were conducted with participants and were audio recorded and transcribed verbatim. Participants were provided a $40 gift card for their time. Interview data were analyzed using a directed content approach, and Cohen's Kappa was obtained (k = 0.924) to signal good inter-rater reliability. Results Results showed renters in gentrified census tracts overwhelmingly viewed gentrification trends as a negative change compared to homeowners. Overall, participants from gentrified census tracts reported being relatively satisfied with their neighborhood, though some suggested there were fewer resources in the neighborhood over time; felt their social cohesion had deteriorated over time; and more commonly reflected negative health changes over time. Conclusions These findings suggest that while gentrification can bring much needed improvements to neighborhoods, it can also bring other disruptive changes that affect the health and wellbeing of existing residents.